Research dilemma in American public administration - Watson, Robert P. (1991)
In the following article, Robert P. Watson presents an interesting account of research dilemma that continues to haunt American Public Administration, that is, while the public administrators there continue to face serious problems, the scholarly research (despite knowledge of administrators' hardship) in the field has failed to assist them by examining coe problems and offering their findings for evolving possible solutions. In this framework, Watson examines research problems confronting the Americans. The major problems discussed by his are: lack of a standard (unified research criterion) guiding the research causing vagueness of research purpose, absence of minimal prioritisation of research functions.
Keywords: Research - United States; Public administration - United States; Public administration